PEMBINAAN KEWIRAUSAHAAN PADA MASYARAKAT TANJUNG GUNDAP RT 02/ RW 01 KELURAHAN TEMBESI, KECAMATAN SAGULUNG - Vargo Christian L. Tobing; Hendri Herman (PUAN INDONESIA, 2021)
Perhaps we have heard that wealthy families will bring up rich children because they are used to being rich. Similarly, some consider that a person becomes a businessman because his fathers, grandparents, and most of his family are descendants of businessmen. This opinion is true and hard to deny because of the environment and lifestyle of the family. But, being an entrepreneur is certainly the right of all human beings. The first step we can take to grow our interest in entrepreneurship is to grow the entrepreneurial spirit in us. There are many ways that can be done, for example through formal education, through entrepreneurship seminars, through training, and self-taught. However, it is not so lucky for the people of Tanjung Gundap, because the people of Tanjung Gundap still have a little formal education. Therefore, to foster entrepreneurial interest in the community Tanjung Gundap RT 02 / RW 01 is to provide counseling, coaching to the community about entrepreneurship so that the community can be motivated to have a business so as to earn additional income. Considering the main source of income of tanjung gundap people is from seafood. If there is no catch of fish, then it is likely that no money is taken home to meet the needs of daily life.